Developmental performance between pediatric cochlear implantation candidates with and without large vestibular aqueduct syndrome. (1st March 2021) - Li, Yanhong; Yang, Yang; Zhang, Wanxia; Sun, Jihang; Liu, Bing; Chen, Min; Liu, Wei; Liu, Shanshan; Wang, Xiaoxu; Li, Shilan; Zhang, Jie; Ni, Xin
Abstract: Background: We are inclined to pay special care and attention to children with large vestibular aqueduct syndrome (LVAS). However, it is not clear whether children with LVAS have more developmental delays than children without LVAS. Objectives: To compare the developmental performance between pediatric cochlear implantation (CI) candidates with and without LVAS. Materials and methods: Medical records of pediatric CI candidates were reviewed. Through propensity score matching analysis, 70 children with LVAS and 70 gender-, age-, and auditory-matched children were recruited as the LVAS and non-LVAS group, respectively. Developmental performances were compared between the two groups. Results: Compared with normal developmental metrics, both LVAS and non-LVAS groups had developmental delay in multiple domains (both p <  .001). Although some differences in motor developments between children with LVAS and without LVAS, they demonstrated overall equal developmental levels in both verbal and nonverbal aspects (all p >  .05). Age of intervention was the primary risk factor for developmental performance of LVAS children ( β <  0, p <  .05) with an obvious delay starting at 1 year of age. Conclusion: Pediatric CI candidates with LVAS had both verbal and nonverbal developmental delays. However, they exhibited similar overall developmental performances to those without LVAS.